Basic logical operation skills and logical reasoning competences of university students in a Western region of Romania - Debrenti, Edith; Bordás, Andrea (Frontiers in Education, 2023)
Empirical research results show that the system of logical operation and conclusion schemes do not become complete even in adulthood. Although we know other logical models besides the classical two-valued logical reasoning model, in higher education for students it is essential to know and apply the rules of the classical reasoning model. Proofs, reasoning and refutation are necessary in the case of several subjects, as scientific language uses a large number of logical operations. Our 2022 end-of-year research measured general logical basic-knowledge and operations in everyday life, mathematical, physical, chemical and biological contexts based on 246 university students’ online testing. The students completed the tasks which required the correct conclusion in the highest proportion (69.02%), followed by the interpretation of ‘at most’/’at least’ (63.41%), and at least the negation (the negation of the ‘at least’, of ‘exists’ and of ‘for all’) (29.91%). Our results show that the correct interpretation did not become dominant in the case of all logical operations for these students. The everyday life problems were solved correctly by the highest percentage of students (70.05%), followed by problems in biological, physical and mathematical context. They were at least successful (28.04%) in solving logical problems in chemistry context. This shows that our data cannot be analysed without the semantic content. Based on different statistical tests, we did not found significant difference in performance between genders, but as according to the human capital theory students of more highly educated mothers performed significantly better.